Cyber Law Awareness Regarding Illegal Access and Data Breaches in Indonesia - Gani, Maria Minerva; Nathania, Cheryl; Dirgantara, Putra; Ritongga, Heigel; Aditya, Rifaldo; Yuri, Nicole; Amira, Tasya; Jhonray, Natasha; Ginting, Yuni Priskila (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
The increasing number of illegal access and personal data breach cases has caused significant losses to the public and contributed to declining public trust in Electronic System Providers (Penyelenggara Sistem Elektronik/PSE). This community service activity focuses on strengthening public understanding of cyber law and raising awareness of personal data protection within the legal framework of the New Criminal Code (KUHP), the Law on Information and Electronic Transactions (UU ITE), and the Law on Personal Data Protection (UU PDP). The purpose of this program is to provide education on the risks associated with the leakage of Personally Identifiable Information (PII), the legal construction of criminal and civil liability for perpetrators and PSEs, as well as the importance of preventive-based system security. The method employed is a narrative juridical approach combined with socialization activities and participatory discussions. This approach is intended to enhance legal awareness, strengthen preventive measures, and encourage responsible digital behavior among community members in order to support the creation of a secure and sustainable digital ecosystem.